The crystal structure of the phosphatidylinositol 4-kinase IIα - Baumlova, Adriana (EMBO Rep, 2014)
Phosphoinositides are a class of phospholipids generated by the action of phosphoinositide kinases with key regulatory functions in eukaryotic cells. Here, we present the atomic structure of phosphatidylinositol 4-kinase type IIα (PI4K IIα), in complex with ATP solved by X-ray crystallography at 2.8 Å resolution. The structure revealed a non-typical kinase fold that could be divided into N- and C-lobes with the ATP binding groove located in between. Surprisingly, a second ATP was found in a lateral hydrophobic pocket of the C-lobe. Molecular simulations and mutagenesis analysis revealed the membrane binding mode and the putative function of the hydrophobic pocket. Taken together, our results suggest a mechanism of PI4K IIα recruitment, regulation, and function at the membrane.